ANALISIS KELAYAKAN FINANSIAL DAN RISIKO PENGEMBANGAN PERKEBUNAN KARET RAKYAT DI KECAMATAN GUNUNG PELINDUNG KABUPATEN LAMPUNG TIMUR - Fatihatun Ni’mah; Wan Abbas Zakaria; Fembriarti Erry Prasmatiwi (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2026)
This study aimed to analyse the financial feasibility and risks of developing smallholder rubber plantations. The study used a survey method in Gunung Pelindung Subdistrict, East Lampung Regency, with data collection conducted from February to April 2025. The research samples were 48 rubber farmers selected using purposive sampling based on the age of the plants. The data analysis method used was financial feasibility analysis (NPV, IRR, Net B/C, Gross B/C, and Payback Period). Risk analysis used the Coefficient of Variation (CV). The results showed that smallholder rubber plantations were financially feasible with an NPV of IDR 96,735,632, an IRR of 12.15 percent, a Gross B/C of 1.36, a Net B/C of 1.96, and a Payback Period of 15.33 years. Sensitivity scenario calculations showed that the development of smallholder rubber plantations in Gunung Pelindung Subdistrict remained feasible with a percentage increase in production costs of up to 39 percent, a decreased in rubber production of up to 46 percent, and a decreased in the selling price of rubber of up to 51 percent. The price risk was classified as low (CV = 0.40), while the production risk was  classified as moderate (CV = 0.50). The greatest source of risk was caused by leaf fall disease, which occurs every year. Risk mitigation efforts were carried out by planting disease-resistant seedlings and applying fertilisers in accordance with government recommendations.  Key words: feasibility, financial, risk, rubber, sensitivity